Intervenções curriculares na perspectiva da abordagem temática: avanços alcançados por professores de uma escola pública estadual do RS - Giacomini, Alexandre (2014)
This research, predominantly qualitative and ethnographic in school life, has as its theme the curriculum and teacher training in teaching. This research is relevant for the importance and need for new curricular settings, based on the critical perspective and social context, have to trigger a process of profound transformation, shaking the linear style and curricular current thinking and for that a continuous and permanent training of teachers is required. The problem of investigation of this research is: What would be the possible progress made by the teachers of a public high school in the city of Restinga Sêca/RS when implementing curricular interventions from the perspective of thematic approach in regular and adult education groups of high school? Based on this question, the following objectives were outlined: to contribute through a formative and collective process with the teachers of Érico Veríssimo School for building curricular interventions guided by the thematic approach; to check with the teachers of this school if they adopt and how they adopt in their daily practice curricular interventions guided by the thematic approach; to analyze the opinions and perceptions of teachers at this school about the progress made when implementing curricular interventions guided by the thematic approach. The research was implemented in a public high school in the city of Restinga Sêca/RS during the year of 2012 and the sample consisted of teachers from the regular high school and adult education (EJA). The theoretical referential that guides the research is grounded in the assumptions of the educator Paulo Freire and in ideals of the educational implications of the movement Science-Technology-Society (STS). The instruments used for data collection were: questionnaire, participant observation (through notes and logbooks/field), document analysis and semistructured interview. Regarding the methodology of data analysis, it was used the Textual Discourse Analysis. The results were presented in the form of categories of advances achieved by teachers in implementing the thematic approach in the daily routine of that school entitled as: the importance of the training course, the theme worked from the reality, from the student(s)' context, the teachers' engagement in collective and interdisciplinary work, the change in concept of curriculum and the dialogue between teacher-student and student-student. By way of conclusion, it is important to emphasize that all these categories contribute to the change of the new style of curriculum thinking, since they are in agreement with the profound process of curricular reconfigurations buoyed in critical perspective and social context. It also highlights a new school space/time provided to the research by the new proposed restructuring of the polytechnic high school state system of Rio Grande do Sul, as well as their convergences and divergences in relation to the Reorientation Curriculum Movement in the city of São Paulo.